2014
DOI: 10.1016/j.proeng.2014.11.787
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Digestion of Kitchen Waste to Produce Biogas

Abstract: Kitchen waste (KW) can be utilized to produce biogas due to its high biodegradability, calorific value and nutritive value to microbes, which will reduce our dependency on fossil fuels. The research work was conducted to investigate the production ability of biogas as an alternative energy from KW with co-digestion of cow manure (CM) through anaerobic digestion (AD). Firstly, three digesters were prepared to observe the individual degradation rate of KW, CM and co-digested KW with CM at room temperature (25°C~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…By comparison, the volume of biogas formed from slurry of cattle dung was less than that formed from kitchen food waste in cattle urine probably due to kitchen food waste providing a better nutrient balance for carbon to nitrogen than cattle dung which was largely lignified cellulose [40]. The microbes survive better in media containing more nitrogen than those containing less because nitrogen is an essential element for their life.…”
Section: Dilnaohmentioning
confidence: 97%
See 3 more Smart Citations
“…By comparison, the volume of biogas formed from slurry of cattle dung was less than that formed from kitchen food waste in cattle urine probably due to kitchen food waste providing a better nutrient balance for carbon to nitrogen than cattle dung which was largely lignified cellulose [40]. The microbes survive better in media containing more nitrogen than those containing less because nitrogen is an essential element for their life.…”
Section: Dilnaohmentioning
confidence: 97%
“…As shown on Figure 3, the rate of evolution of biogas from mixed aqueous slurry of cd and kwf was higher than single substrate because the combination brought together the positive characteristic of feed stocks and potentially bringing better digestion performance as well as more rapid growth of microbial population in the mixed substrate than in the single substrate [40,44].…”
Section: Figure-3 Plot Of Rate Of Biogas Formation Against Timementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it must be mentioned that co-digestion of FW with other household waste streams has not been considered. In spite of literature has demonstrated that specific biogas yield (SBY) is certainly improved by co-digestion (Iqbal et al, 2014) the potential inhibition of AD (e.g. detergents or papers towels) would make the proposal less reliable (Chen et al, 2008).…”
Section: The Proposalmentioning
confidence: 99%